2021
DOI: 10.21037/mhealth-19-191
|View full text |Cite
|
Sign up to set email alerts
|

Apps for individuals diagnosed with breast cancer: a preliminary assessment of the content and quality of commercially available apps in Spanish

Abstract: Background: many apps are directly related to health issues. Recent studies show that apps are widely accepted by the population and contribute to the modernization of the healthcare system. However, before recommendation, their contents and quality should be assessed, as well as the behavioral change techniques they include. In Spain, no study has been found to determine which apps are aimed at addressing any aspect of breast cancer. The objective of this study was to identify and describe the contents and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Others have similarly identified many apps with just about acceptable scores among breast cancer prevention apps. 41 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…Others have similarly identified many apps with just about acceptable scores among breast cancer prevention apps. 41 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…A recent Spanish study tested 6 apps (2 on iOS, 5 on Android, and 1 on both) using the MARS framework. The results of the study showed relatively diverse scores, with an objective quality mean score of 3.06 and a subjective quality mean score of 1.96 [ 52 ]. Another study evaluated the quality of mHealth apps for educational purposes in Iran using the MARS framework.…”
Section: Discussionmentioning
confidence: 99%